Time and travel costs incurred by women attending antenatal tests: A costing study. (September 2016) - Verhoef, Talitha I.; Daley, Rebecca; Vallejo-Torres, Laura; Chitty, Lyn S.; Morris, Stephen
Abstract: Objective: to estimate the costs to women, their friends and family for different antenatal tests in the Down's syndrome (DS) screening pathway. Design: questionnaire-based costing study. Setting: eight maternity clinics across the UK. Participants: pregnant women ( n =574) attending an appointment for DS screening, NIPT or invasive testing between December 2013 and September 2014. Measurements: using data collected from the questionnaires we calculated the total costs to women by multiplying the time spent at the hospital and travelling to and from it by the opportunity costs of the women and accompanying person and adding travel and childcare costs. Assumptions about the value of opportunity costs were tested in one-way sensitivity analyses. The main outcome measure was the mean cost to the women and friends/family for each test (DS screening, NIPT, and invasive testing). Findings: mean costs to women and their family/friend were £33.96 per visit, of which £22.47 were time costs, £9.15 were travel costs and £2.34 were childcare costs. Costs were lowest for NIPT (£22), £32 for DS screening (£44 if combined with NIPT), and highest for invasive testing (£60). Sensitivity analysis revealed that variations around the value of leisure time opportunity costs had the largest influence on the results. Key conclusions: there are considerable costs to women, their friends and family when attending different tests in the DS screening pathway. Implications for practice: when assessing the cost-effectiveness of changes to this pathway, costs to women should be considered. Highlights: On average, women spent 71 minutes at the clinic to have their test. Average costs to the woman and her family/friends were £33.96. The costs were lowest for NIPT (£22) and highest for invasive testing (£60). The value of leisure time has a large impact on the costs.